Histories of Medieval European Literatures: New Patterns of Representation and Explanation - Paolo Borsa; Christian Høgel; Lars Boje Mortensen; Elizabeth Tyler; Simon Gaunt; Panagiotis A. Agapitos; Stephan Müller; Pavlína Rychterová; Benoît Grévin; Enrico Fenzi; Ryan Szpiech; Thomas Ricklin; et al. (Interfaces: A Journal of Medieval European Literatures, 2015)
Interfaces: A Journal of Medieval European Literatures is invested in bringing together the linguistic, literary, and historical expertise to take a European approach to medieval literature. The journal aims to establish a forum both for articles which move across literatures (plural) and also, more ambitiously, to foster reflections on a more elusive, but no longer entirely absent, object, European medieval literature (singular). In line with the journal’s scope and vision to promote integrated approaches to European medieval literatures, we begin by facing head-on the multiple challenges of devising new types of narratives about medieval textual cultures. We have invited papers which take a wider regional perspective and move across medieval Europe as well as papers which bring an explicitly European perspective to more specific topics (with a tighter thematic, chronological, geographic, or linguistic focus).